RELATIONSHIP BETWEEN POST SECTIO CAESAREA MATERNAL PAIN AND BREASTFEEDING AT MGR.GABRIEL MANEK SVD HOSPITAL ATAMBUA - Ngatwati, Ngatwati; Ningtyas, Woro Setia; Sampurna, Mahendra Tri arif; Djuari, Lilik (Siklus : Journal Research Midwifery Politeknik Tegal, 2025)
The pain experienced by the mother can result in the mother being reluctant to breastfeed her baby as soon as possible and preferring to focus on herself. This study aims to analyze the relationship between post sectio caesarea pain and breastfeeding at MGR.Gabriel Manek SVD Hospital Atambua. The method used a cross sectional approach. The  population in this study were post Sectio Caesarea mothers in the Anggrek room at MGR. Gabriel Manek SVD Hospital Atambua from May to June 2023. Based on existing criteria, sampling was carried out using a purposive sampling technique, a sample of 85 data were obtained. Data collection techniques were carried out using a questionnaire. Data analysis used univariate analysis was used to describe post-sectio caesarea maternal pain and to describe breastfeeding, while bivariate analysis used the Spearman correlation test to look for the relationship between pain and breastfeeding. The results of statistical analysis using the spearman correlation test, obtained a p value 0,001 (p value 0,05), which means there is a significant relationship between maternal pain after caesarean section and breastfeeding. The result of the correlation coefficient are 0,771, which shows that maternal pain after caesarean section and breastfeeding has a strong relationship.